Managing fashion : a management perspective - Hameide, Kaled K. (New York, NY : Routledge, 2021)
"The fashion industry is a multibillion-dollar global industry with a variety of organizational structures and a multitude of challenges. Such scope triggered the recent rise in management programs in the US and Europe aiming to produce and train young managers to meet such global and diverse challenges. Managing Fashion covers the fashion business with a twist - a management twist. Its goal is to tackle the topics from a fashion manager perspective referencing relevant management concepts and theories thus offering a deeper and more practical dimension to the addressed issues. It offers a balanced mix of fashion and management, theory and application, as well as creating an opportunity for analysis and critical thinking. Discussions throughout the book will be supported by specially developed case studies and relevant examples taken from the fashion industry. It is an opportunity to expose the fashion student or reader as well as aspiring fashion managers to a more practical approach to fashion theories and issues. Managing Fashion will serve as a core text for Fashion Studies, Fashion Entrepreneurship, and Fashion Merchandising majors as well as for special business degrees and management certificates targeting the fashion industry"--
OCLC-licensed vendor bibliographic record.
Keywords: Fashion merchandising -- Management; Clothing trade -- Management; Strategic planning; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Industries / Textile Industry